Lipoproteiny osocza chorych z niewysiękową postacią AMD leczonych miejscowo betablokerami - Gębka, Andrzej; Iwaszkiewicz-Bilikiewicz, Barbara; Raczyńska, Krystyna; Homziuk, Magdalena; Ciechanowski, Cezary (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Reduced perfusion in the choroidal vessels has been proposed as the vascular pathogenesis for AMD. As no specific therapy is currently available, the authors decided to evaluate the possible benefits of topically administrated betaxolol in non-exudative AMD patients. 114 randomly selected patients with NE AMD was divided into 2 groups: group I (64 patients) and group II (50 patients). The subjects in group I have been treated with topical 0,5% betaxolol, while in the group II with artificial tears twice daily for one year. None of the patients had received prior topical or systemic treatment lowering IOP. The subjects in both groups had follow-up for 1 year, during which lipoproteins' profile sampling was performed twice at baseline and after 52 weeks. Both, baseline and outcome measures included: complete ophthalmologic examination. The changes in serum lipoproteins levels varied, but the statistical analyze did not show the significant differences.